Concealed gallbladder perforation: a rare case report. Issue 6 (22nd June 2021) - Suleiman, Jamil; Mremi, Alex; Tarmohamed, Murad; Sadiq, Adnan; Lodhia, Jay
Abstract: Acute acalculous cholecystitis remains an elusive clinical diagnosis possibly due to complex clinical setting in which this entity develops, lack of large prospective controlled trials that evaluate various diagnostic modalities, thus dependence on a small database for clinical decision making. Concealed gallbladder perforation is rare. Herein, we report an 82-year-old female who presented with a right upper quadrant pain and features of local peritonitis. Abdominal ultrasound was suggestive of cholecystitis while computed tomography (CT) scan reported a perforated gallbladder with pericholecystic fluid collection. The patient underwent successful cholecystectomy; and intra-operatively, similar findings as those reported on imaging were seen. Unfortunately, she succumbed shortly post-operatively due to pulmonary embolism. Our report highlights the importance CT scan in patients with vague abdominal symptoms followed by sudden resolution. It also reminds the importance of considering the diagnosis of concealed gallbladder perforation as a differential in patients with peritonitis, as it may be missed by routine radiological investigations.